KS0 and Λ(Λ‾) two-particle femtoscopic correlations in PbPb collisions at sNN=5.02TeV - KAYA, MİTHAT (My University, 2024)
Two-particle correlations are presented for KS0, [Formula presented], and [Formula presented] strange hadrons as a function of relative momentum in lead-lead collisions at a nucleon-nucleon center-of-mass energy of 5.02 TeV. The dataset corresponds to an integrated luminosity of 0.607nb−1 and was collected using the CMS detector at the CERN LHC. These correlations are sensitive to quantum statistics and to final-state interactions between the particles. The source size extracted from the KS0KS0 correlations is found to decrease from 4.6 to 1.6 fm in going from central to peripheral collisions. Strong interaction scattering parameters (i.e., scattering length and effective range) are determined from the [Formula presented] and [Formula presented] (including their charge conjugates) correlations using the Lednický–Lyuboshitz model and are compared to theoretical and other experimental results.
Keywords: Fizik; Temel Bilimler; Physics; Natural Sciences; Temel Bilimler (Sci); Fizik Nükleer; Natural Sciences (Sci); Physics Nuclear; Nükleer ve Yüksek Enerji Fiziği; Fizik Bilimleri; Nuclear and High Energy Physics; Physical Sciences; CMS; Femtoscopy; Heavy ion; Scattering parameters; V0